FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN KERJA PEGAWAI PADA DINAS PEMUDA OLAHRAGA PARIWISATA DAN KEBUDAYAAN (DISPORAPARBUD) KABUPATEN KERINCI - Bustami, Edwin (journal of RESIDU, 2018)
The level of employee satisfaction is one of the important and influential dimension in operational departments or agencies as a whole. Therefore youth sports department of tourism and culture always consider the Kerinci district employees job satisfaction, where the lack of job satisfaction were identified with high levels of absenteeism, high turnover, a delay in the work or service which is not friendly. This study aims to determine the factors that affect the level of employee satisfaction in youth sports department of tourism and culture Kerinci district, this research is done by analyzing the job description of the challenge, the reward system is fair, supportive working atmosphere, the attitude of coworkers either individually or jointly effect on the level of employee satisfaction in youth sports department of tourism and culture Kerinci district. Research was conducted in Kerinci district office disporaparbud with quantitative research approach that gives an overview of research results in the form of numbers by using respondents consisting of civil servants by 43 people through the interview method of data collection and filling questionnaires. The analysis technique used is regression analysis in assisted processing using SPSS version 19.00. The results showed that factors related to employee job satisfaction factors work challenge, reward system that is fair, supportive working atmosphere, the attitude of co-workers are all positive effect on the level of employee job satisfaction, but the most influential factor reward system is fair.